How sleep and fatigue shape statements in evidence: A psycho-legal perspective - Krizan, Zlatan; Curran, Breanna (Frontiers in Cognition, 2024)
Testimonial evidence in the form of verbal accounts by victims, witnesses, and suspects plays a critical role in investigations and judicial proceedings, often serving as the only evidence during a trial. The psychological nature of testimonies causes this form of evidence to be inherently limited, motivating psycho-legal scholars to identify both risk factors and solutions necessary to improve its reliability. To this end, the current perspective argues that sleep-related fatigue is a formative factor that influences the fidelity of statements and confessions provided during legal interactions. Specifically, it considers the prevalence of sleep disruption among subjects interacting with the criminal justice system, its likely impact on memory of victims and witnesses, and the role of sleep deprivation in confessions. In view of legal doctrines relevant to both evidentiary and constitutional considerations, this analysis is meant to motivate future work at the intersection of sleep-related fatigue and legal processes.